Argument on behalf of the Women's rights program - Ruth Ehrlich::::::
This document presents an argument defending the urgency of adopting the Women's Rights Program, asserting that women's equality is a critical issue despite competing political crises. It highlights the compounded discrimination faced by women, particularly poor women and women of color, and calls for reforms in welfare, employment, child care, and housing policies. The text emphasizes persistent workplace inequality, citing wage disparities, occupational segregation, and ongoing sex discrimination despite existing civil rights laws. It also advocates for women's control over their own bodies, including access to birth control and abortion, arguing that restrictive laws harm women and society. Finally, the document contends that greater participation of women in political decision-making could temper aggression and militarism in public policy, potentially leading to more humane and life-preserving governance.